Inclusión de estudiantes migrantes en escuelas públicas, visto desde la mirada del profesorado de Arica, Chile - Aguilera Barraza, René; Tobar Quezada, Patricio; Rojas Merida, Luis (Universidad de Costa Rica, 2023)
The increase in foreign migration to Chile produced a consolidation of a culturally and nationally diverse student population in the educational reality, between 2018 and 2020. The government, faced with the need to manage the difference within school communities, implemented a series of measures to facilitate the inclusion of migrant students, highlighting the national policy for foreign students, whose purpose is to guarantee the right to education for migrant children and adolescents. In this scenario, the objective of the article is to review teacher perceptions about the process of inclusion of foreign students in public schools in the north of Arica. The research has a qualitative cut, with phenomenological roots, and used the semi-structured interview to collect data. The study sample from the saturation process is 7 people. The results of the research indicate: First, that after five years of enactment of the national policy of foreign students there is no full cultural change to manage diversity. Second, although teachers from personal initiatives seek to recognize migrant children and adolescents in their particularities, the schools investigated still resort to a pedagogical approach to assimilation to respond to diverse students; and third, despite efforts to promote an appreciation of cultural difference in the educational centers investigated, practices of discrimination and exclusion of migrant students persist, impeding an adequate process of school inclusion.